A Rare Case of Stenosis at the Inferior Vena Cava to Right Atrium Anastomosis After Bicaval Orthotopic Heart Transplantation. (December 2019) - Abrams, Benjamin; Hoffman, Jordan; Aftab, Muhammad; Evers, Jacob; Seres, Tamas
Stenosis at either the superior or inferior caval anastomosis is a rare complication of orthotopic heart transplantation (OHT) and is unique to the bicaval surgical technique. The severity of stenosis dictates the degree of clinical significance, varying from asymptomatic to congestive end-organ injury and hemodynamic instability from impaired preload. Due to differences in the anatomic location of organ congestion, the clinical presentation also depends on which of the 2 anastomoses is involved. In this article, the authors describe a case of stenosis at the inferior vena cava to right atrium anastomosis, which was diagnosed intraoperatively during OHT after weaning from cardiopulmonary bypass. Transesophageal echocardiography provided an accurate and timely diagnosis of this complication, which allowed for immediate surgical correction. Surprisingly, a large, native Eustachian valve was found to be obstructing the anastomosis. Resection of the valve relieved the previously significant narrowing across the anastomosis. This case highlights the importance of thorough intraoperative transesophageal echocardiographic evaluation of graft anastomoses during OHT, as well as an understanding on the part of the echocardiographer of the specific surgical techniques employed during OHT.